Macrophage scavenger receptor A mediates adhesion to apolipoproteins A-I and E. - Neyen, C; Plüddemann, A; Roversi, P; Thomas, B; Cai, L; van der Westhuyzen, DR; Sim, R; Gordon, S (2009)
Macrophage scavenger receptor A (SR-A) is a multifunctional, multiligand pattern recognition receptor with roles in innate immunity, apoptotic cell clearance, and age-related degenerative pathologies, such as atherosclerosis and Alzheimer's disease. Known endogenous SR-A ligands are polyanionic and include modified lipoproteins, advanced glycation end products, and extracellular matrix proteins. No native plasma ligands have been identified, but it is known that SR-A recognition of unidentified serum components mediates integrin-independent macrophage adhesion, which may drive chronic local inflammation. In this study, we used a high-throughput fractionation and screening method to identify novel endogenous SR-A ligands that may mediate macrophage adhesion. SR-A was found to recognize the exchangeable apolipoproteins A-I and E (apo A-I and apo E, respectively) in both lipid-free and lipid-associated form, suggesting the shared amphipathic alpha-helix as a potential recognition motif. Adhesion of RAW 264.7 macrophages to surfaces coated with apo A-I and apo E4 proved to be integrin-independent and could be blocked by anti-SR-A antibodies. The presence of apo A-I and apo E in pathological deposits, such as atherosclerotic lesions and neurotoxic Alzheimer's plaques, suggests a possible contribution of SR-A-dependent adhesion of macrophages to an inflammatory microenvironment.